Pengaruh Media Youtube Terhadap Minat Belajar Mahasiswa - Ary Santri Yuanda; Yulia Imanita; Dita Sucinta Sembiring; Ali Ikhwan (Jurnal Pendidikan, Sains Dan Teknologi, 2023)
: The benefit of video learning is the visual and audio presentation of an idea or event to students in the classroom. Youtube is one of the most popular video sharing services on the internet today. The use of YouTube as a learning medium can be considered effective by students in increasing interest and understanding of learning concepts. The research method used in this study was to conduct a literature review of 10 journal articles with a collaborative team that have been published on several websites over the last 5 years. Articles were searched and evaluated using a literature review in a format that included the number, year of the article, title of the article, research objectives, sample size, research variables, research methods, and research results. In fact, many students are more interested in learning and exploring a theory or discussion when delivering material through YouTube videos is chosen as the best teaching medium to make it easier for students. . In English. audiovisual to accommodate all student learning styles, not only to accommodate learning styles, but students to be able to participate directly in interactive discussions and activities, such as noting the importance of each subject, finding words that are hard to find when watching videos, having a desire to read or look for other materials related to YouTube videos or content that are used as learning media. Education plays a very important role in developing quality human resources.